REALITY SHOW AS A TYPE OF MEDIA DISCOURSE (A STUDY OF THE REALITY SHOW KEEPING UP WITH THE KARDASHIANS) - L.M. Ikalyuk; O.I. Doronyuk (Vasyl Stefanyk Precarpathian National University, 2015)
The article focuses on defining peculiarities of the US reality show as a type of media discourse. Based on a study of the reality show Keeping up with the Kardashians, an attempt has been made to determine intralinguistic and extralinguistic factors of creating an image of an ordinary American family in order to attract the public attention.